Motor intervention in children with school learning difficulties - Fernani, Deborah Cristina Gonçalves Luiz; Prado, Maria Tereza Artero; Fell, Rayza Fabiane [UNESP]; Dos Reis, Nelline Largueza [UNESP]; Bofi, Tânia Cristina [UNESP]; Ribeiro, Eliane Beraldi; De Toledo Blake, Márcia; De Mello Monteiro, Carlos Bandeira (My University, 2013)
This study sought to evaluate motor development in children aged 6 to 11 years with learning difficulties and school characteristics of delayed motor development, before and after application of a motor intervention program. The sample consisted of 28 children with a mean age of 107.21 ± 16.56 months, who were evaluated by the Motor Development Scale and received motor intervention for 6 months, followed by reassessment. We observed a statistically significant difference between the average of the motor activity ratios in all areas of the evaluation and reevaluation. Also verified in the evaluation were the concentration ratios of children with motor activity greater than or equal to 80 and there was a revaluation increase in this concentration on re-evaluation, the areas with the greatest increase in concentration and significant differences being: Body Schema, Space and temporal Organization. In the overall evaluation of MDS, most children presented the classification of low normal. However, in the reassessment most have evolved into the average normal, only 4 of themremaining in the same classification. Therefore, in this study, children with learning disabilities also showed motor deficits and the intervention applied contributed to an increase in the motor ratios with consequent improvement in motor development. Besides psychopedagogical asistance, it is essential to reassess them and if necessary apply the intervention in the motor development of children with learning difficulties.
Keywords: Child development; Intervention; Learning